2005
DOI: 10.1097/01.prs.0000169697.06498.df
|View full text |Cite
|
Sign up to set email alerts
|

Free Perforator Flaps in Children

Abstract: In children, as in adults, perforator flaps are a valuable alternative to the traditional muscle or myocutaneous free flap. Because of the added advantage of reducing donor-site morbidity, perforator flaps have become the authors' preferred option in reconstructive cases in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 28 publications
0
64
0
1
Order By: Relevance
“…Initial concerns as to the feasibility and reliability of these procedures were overcome rapidly. [3,4,7] Microsurgeries succeed in children more often than in adults for two reasons. The first issue is that the relative size of the vessels when compared with the child's body is greater than that of adults, and the second issue is that children have minimal comorbidities like smoking, diabetes, hypertension, or peripheral vessel disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial concerns as to the feasibility and reliability of these procedures were overcome rapidly. [3,4,7] Microsurgeries succeed in children more often than in adults for two reasons. The first issue is that the relative size of the vessels when compared with the child's body is greater than that of adults, and the second issue is that children have minimal comorbidities like smoking, diabetes, hypertension, or peripheral vessel disease.…”
Section: Discussionmentioning
confidence: 99%
“…The perforator vessels can be relatively small in children, though their relative size compared with the size of the child's body is greater than that in adults. [7] Our current study reports a series of 30 free flaps performed in children for various reconstructions. Seven of these flaps were perforator flaps, which are valuable reconstructive options even in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…3,15,16 Van Landuyt et al 17 showed that the size of the pedicle vessel in children is larger than in adults in relation to their body size. In addition, pediatric blood vessels tend to be in better condition compared with adults, because of the lack of comorbidities (arteriosclerosis, diabetes, hypertension, smoking, and alcohol abuse).…”
Section: Discussionmentioning
confidence: 99%
“…The free tissue transfers included 12 patients with various etiologies: congenital defects (4), trauma (6), and tumor resection (2). Four patients involved six toe-tohand transfers of the isolated second toe (3) and the combined second and third toe (1) between the age of 5 and 12 years.…”
Section: Methodsmentioning
confidence: 99%
“…1 Free flap surgery in the pediatric population has gained widespread acceptance after an initial period of concern regarding the technical feasibility and reliability of the procedure. 2 The feasibility of free tissue transfers in children is accepted by all authors. 3 Advances in microsurgical techniques have permitted replantation and reconstructive procedures to restore injured parts with a high degree of success rate in children.…”
mentioning
confidence: 99%